2019
DOI: 10.1055/s-0039-1693922
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Mandibular Ramus Dimensions to Lower Third Molar Impaction

Abstract: Objectives The aim of this study was to investigate the mandibular ramus features that could contribute to the etiology of mandibular third molar impaction. Materials and Methods Two hundred and forty subjects were divided into two groups: impacted group: 115 subjects presented with an impacted mandibular third molar, and control group: 125 subjects with the normal mandibular third molar eruption. Digital panoramic radiographs were used, and four angular and twelve linear measurements were done. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
(42 reference statements)
4
19
0
Order By: Relevance
“…Some reports have found a more acute gonial angle in the impacted group than in the normal group, 17 something which was not found in our groups. Our findings are consistent with those obtained by Al-Gunaid et al., 11 who failed to identify any association between the magnitude of the gonial angle and third molar impaction. However, this does not support the results of Behbehani et al., 2 who reported that a small mandibular plane and gonial angle are correlated with an increased chance of third molar impaction.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Some reports have found a more acute gonial angle in the impacted group than in the normal group, 17 something which was not found in our groups. Our findings are consistent with those obtained by Al-Gunaid et al., 11 who failed to identify any association between the magnitude of the gonial angle and third molar impaction. However, this does not support the results of Behbehani et al., 2 who reported that a small mandibular plane and gonial angle are correlated with an increased chance of third molar impaction.…”
Section: Discussionsupporting
confidence: 93%
“…This outcome is supported by Al-Gunaid et al. 11 who attributed the result to the smaller angle between the condyle and coronoid process and longer ramus heights in the control group than those in the impacted group (this results in less backward and forward slope of the posterior and anterior margins of the ramus in the control group). Subsequently, this suggests that the sigmoid notch depth in the control group is more likely to be more in-depth.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations